Prevalence and Antibiotic Susceptibility Pattern of Salmonella Enterica Isolated from Apparently Healthy Students Screened for Salmonella Agglutinins - Musa Yakubu Tula*1, Zulkifli Muhammed Usman 3, Zainab Mohammed Chiroma 1, Richard Elisha 2, Evangeline Ogonna Okpalauwaekwe 1, and Mary Ngozi Ogu 1 (Sokoto Journal of Medical Laboratory Science)
Infections caused by Salmonella enterica remains a major public health concern worldwide, contributing to the economic burden of both industrialized and underdeveloped countries through the costs associated with surveillance, prevention and treatment of disease. This was a cross-sectional study conducted between October – December, 2021 in which the detection of Salmonella enterica by stool culture was carried out on sixty (60) apparently healthy students screened for Salmonella agglutinin by widal agglutination test. The susceptibility of the Salmonella isolates to commonly used antibiotics was carried out by disc diffusion method. The result showed that 52 (82.7%) subjects were found to be widal positive with at least one of the tested antigens. From these, 26 (86.7%) each were recorded among male and female students respectively. The most common Salmonella agglutinin detected in both male and female belong to the Paratyphi serovar. However, the percentage of the positive titres, 1:320 and 1:160 in both males (p=0.139). and females (p =0.382) were not significantly different. Salmonella enterica was isolated in 11(42.3%) males and 7(26.9%) females, with a combined prevalence of 18(34.6%). For male subjects, Salmonella enterica was more susceptible to ciprofloxacin (81.8%) and ofloxacin (81.8%) and least to nalidixic acid (45.5%). For female gender, Salmonella enterica was more susceptible to gentamycin, augmentin, ofloxacin, streptomycin, and cotrimoxazole with 71.4% susceptible rate each, but more resistant to nalidixic acid (85.7%) and ampicillin (71.4%). The result also showed that 11 of the Salmonella enterica exhibits multidrug resistance phenotype, accounting for the prevalence of 64.7%. From these, the MDR phenotype was more in female than male but with no statistical difference (P=0.569). The findings of this study established that Salmonella agglutinins are common among apparently healthy. It also shows the limitations of widal agglutination test, since Salmonella species could not be isolated in all the subjects whose sera were widal positive.